Importer et diffuser la littérature scientifique européenne en Géorgie dans la seconde moitié du XIXe siècle : le discours de vulgarisation de la presse géorgienne - Tamara Svanidzé (Amnis)
My work shows in what measure the Georgian press during the second half of the nineteenth century, which constitutes a precious historical resource for the study of time period, offers a global view of the evolution of cultural transfers from Europe to Georgia in the field of popular science. It analyzes the principal mechanisms that allow the flow of ideas in this field, such as the elaboration of a new terminology, the establishment of selection criteria for foreign texts, and development of the discursive strategies facilitating the diffusion of such texts. It also examines the different modes of referring to European scientific modernity. As I clarify the underlying criteria that guide the selection of texts that are translated or the choice of references. I try to show how Georigan discourse about science developed, reflecting a historical context characterized by the emergence of a national consciousness and competing ideologies. I will try to understand in what manner the translators, who were at the same time contributors to the most important periodicals and eminent figures in the modernization of the country, use these discourses of scientific popularization to reinforce their position in the emerging Georgian intellectual system.